Upaya Meningkatkan Minat Belajar Pendidikan Pancasila Melalui Model Teams Games Tournament (TGT) di SMA Negeri 14 Surabaya - Mia Fitria Nisa'Q; Maskanijanto Maskanijanto; Harmanto Harmanto (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research was motivated by the low interest of students in Pancasila Education subjects in class X-2 SMA Negeri 14 Surabaya, due to conventional teaching methods, the use of technology that is not maximized and the delivery of material that is less relevant to real life. This research is a Classroom Action Research (PTK) using a descriptive qualitative approach involving students of class X-2 SMA Negeri 14 Surabaya as the subject. The research process was conducted with a pre-cycle, two cycles with planning, implementation, observation and reflection. Data collection techniques using observation and questionnaire. The results showed that the application of the Teams Games Tournament (TGT) type cooperative model was able to increase students' interest in learning. The questionnaire data shows an increase in learning interest from 49.28% (pre-cycle) to 62.03% (cycle I) to 76.39% (cycle II). The increase can be seen from the involvement of students in group activities, cooperation during the game. In addition to data based on questionnaires, students can show their enthusiasm in participating in learning, because learning is carried out interactively. The results of this research show that the model used is able to increase students' interest in learning Pancasila Education subjects.